问题
Hi i'm trying to figure out how to calculate the inverse of a quaternion. A code example would be awesome.
Cheers
回答1:
See Wikipedia article for the entire Quaternion math.
Don't know what language you want to use but I'll try to give some hints in Haskell.
data Quaternion = Q Double Double Double Double deriving (Show, Eq)
First, you need to implement multiplication and addition of quaternions.
instance Num Quaternion where
(+) = q_plus
(*) = q_mult
--....
q_plus (Q a b c d) (Q a' b' c' d') = Q (a + a') (b + b') (c + c') (d + d')
q_mult (Q a b c d) (Q a' b' c' d') = Q a'' b'' c'' d''
where
a'' = a * a' - b * b' - c * c' - d * d'
b'' = a * b' + b * a' + c * d' - d * c'
c'' = a * c' - b * d' + c * a' + d * b'
d'' = a * d' + b * c' - c * b' + d * a'
Multiplication with scalar should be done via a conversion:
scalar_to_q a = Q a 0 0 0
Define
i = Q 0 1 0 0
j = Q 0 0 1 0
k = Q 0 0 0 1
Then implement the conjugate and modulus:
q_conjugate q = (scalar_to_q (negate .5)) * (q + i * q * i + j * q * j + k * q * k)
q_modulus q = sqrt $ q * (q_conjugate q)
Now, the inverse:
q_inverse q = (q_conjugate q) * (scalar_to_q (m * m))
where
m = q_modulus q
Hope it's useful.
PS: the instance definition above will simplify things a little if completed successfully. I let you fill in the gaps.
回答2:
Look at the Matrix and Quaternion FAQ. There are some code samples as well.
来源:https://stackoverflow.com/questions/6689967/calculate-quaternion-inverse